Monitoring land motion due to natural gas extraction: validation of the intermittent SBAS (ISBAS) DInSAR algorithm over gas fields of North Holland, the Netherlands - Gee, David; Sowter, Andrew; Novellino, Alessandro; Marsh, Stuart; Gluyas, Jon (Elsevier, 2016)
The differential interferometric synthetic aperture radar (DInSAR) remote sensing technique has proven to be invaluable in the remote monitoring of earth surface movements associated with the extraction and geostorage (subsurface injection) of natural resources (water, oil, gas). However, a significant limitation of this technique is the low density and uneven coverage that may be achieved over vegetated rural environments. The Intermittent Small Baseline Subset (ISBAS) method, an amended version of the established SBAS algorithm, has been designed to improve coverage over rural, vegetated, land cover classes by allowing for the intermittent coherence that is predominant in such areas. In this paper we perform a validation of the ISBAS method over an area of gas production and geostorage in North Holland, the Netherlands. Fortytwo ERS-2 (SAR) C-band images (1995-2000) and 63 ENVISAT (ASAR) C-band images (2003-2010) were processed using the ISBAS technique and the derived measurements enabled the identification of subsidence patterns in rural and urban areas alike. The dominant feature was an area of subsidence to the west of Alkmaar, attributed to natural gas production from the Bergermeer reservoir, where subsidence rates in the region of 3 mm/year were measured. Displacements derived using linear and non-linear surface deformation models were validated with respect to the first order system of levelling benchmarks which form the Amsterdam Ordnance Datum (NAP). It was established that ISBAS products were accurate to within 1.52 mm/year and 1.12 mm/year for the ERS and ENVISAT data sets respectively. Error budgets were comparable to results using persistent scatterers interferometry (PSI) during a validation activity carried out in the European Space Agency Terrafirma project. These results confirm the capability of the ISBAS method to provide a more regular sampling of land motion measurements over gas fields that may be critically used in future to infer the properties of buried, fluid-filled, porous rock.